Model dan Proses Pengembangan Entrepreneurship Di Kawasan Pantai Pandawa Desa Adat Kutuh - Ni Putu Lilik Suandewi (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis study analyzes the model and process ofbusiness development that has been advanced so that information users can know how to manage a business. The purpose of this research is to know the model of entrepreneurship development and entrepreneurship development process at Pandawa Beach Desa Adat Kutuh. This research is done by deep interview method and the type ofresearch used is qualitative. In this research, the data analysis technique used is descriptive qualitative analysis. Informants in this research are Bendesa Adat Kutuh, Kepala Desa Adat Kutuh, and Pandawa Beach Manager. The results showed that 1) The model of entrepreneurship development conducted at Pandawa Beach Kutuh Custom Village based on the concept of togetherness. The concept of togetherness is what is meant by society, by society and for society. 2) The development process makes Kutuh people more creative and more observant to see the opportunities available to open a new business. Development process is divided into development stages consisting of innovation process, trigger process, implementation process, and growth process.